2021
DOI: 10.30572/2018/kje/090411
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Effect of Welding Electrode Types on Tensile Properties of Low Carbon Steel Aisi1010

Abstract: This paper discussed the effect of welding variables on the heat-affected zone (HAZ) by using a tensile test of welded 10 mm thick low carbon steel AISI1010 commercial plate, which is welded using the Shielded Metal Arc Welding (SMAW) method. Different welding electrodes E6013 and E7018 were considered as welding parameters investigated. After that, the welded specimens were cut and machined to standard configurations for tensile test. The results showed that selecting different welding electrodes had a remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…So that, its strength is low. This is because in the joint area occurred the concentration of stress on the weld [21][22]. So that the mechanical properties change such as ductile properties change to brittle, thus during the tensile test the joint area easily to break.…”
Section: Discussionmentioning
confidence: 99%
“…So that, its strength is low. This is because in the joint area occurred the concentration of stress on the weld [21][22]. So that the mechanical properties change such as ductile properties change to brittle, thus during the tensile test the joint area easily to break.…”
Section: Discussionmentioning
confidence: 99%
“…After surveying the former literature, articles [11,12] were found dealing with the study of the influence of electrode type on the microstructure and mechanical behavior of austenitic stainless steel welds achieved using the SMAW process. Other researches [13][14][15][16][17] have focused on shielded metal arc low carbon steel welds by the use of different electrodes. The significant influence of electrode type and welding current on the microstructure and mechanical properties of these welds has been clearly revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Current researches in SMAW single pass welding are such as by Nassar et al [3]. They performed an experimental study on the effect of electrode types on tensile properties of low carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes showed that, the mechanical properties; such as the UTS, yield strength and elongation percentage of the welded specimens, were remarkably influenced by different welding electrodes. They concluded that the fracture toughness of welded specimen in E6013 join was found to be better compared to the welded specimen in E7018 join and the specimens that welded using the E6013 electrode displays better UTS [3].…”
Section: Introductionmentioning
confidence: 99%